Airy pattern on narrow photoluminescence spectrum of band to band recombination in CdTe:Te thin films - Becerril-Silva, M. (2018)
Semiconductor CdTe:Te films were deposited by means of rf sputtering on glass substrates. The excess of Te gave place to a high number of Cd-vacancies (VCd) producing p-type CdTe films. The density of carriers produced a high strength surface electric field which allowed obtain the bandgap value employing modulated transmittance spectroscopy. The obtained bandgap value of 1.40 ± 0.01 eV was confirmed by absorption spectroscopy measures. The density of holes is so high that bandgap renormalization is observed. Photoluminescence (PL) measurements were carried out with the down-converted 883.2 nm (1.403 eV) line of the 441.6 nm wavelength of a He-Cd laser. This energy allows to produce a resonant excitation of the CdTe:Te films, in such a way that electrons from the conduction band (CB) can be just excited to the valence band (VB). The resonant excitation produced a PL spectrum of band to band electron-hole recombination showing discrete energy emissions that follow the pattern of oscillations corresponding to the Airy model for a quantum triangular potential well. The average width of signals of the higher energy oscillations is 12 ± 3 μeV and separation between energy levels is of the order of 12 ± 3 μeV.